The Role of the Endoplasmic Reticulum in Peroxisome Biogenesis - Dimitrov, Lazar (Cold Spring Harbor Laboratory Press, 2013)
Peroxisomes are essential cellular organelles involved in lipid metabolism. Patients affected by severe peroxisome biogenesis disorders rarely survive their first year. Genetic screens in several model organisms have identified more than 30 PEX genes that are required for the formation of functional peroxisomes. Despite significant work on the PEX genes, the biogenic origin of peroxisomes remains controversial. For at least two decades, the prevailing model postulated that peroxisomes propagate by growth and fission of preexisting peroxisomes. In this review, we focus on the recent evidence supporting a new, semiautonomous model of peroxisomal biogenesis. According to this model, peroxisomal membrane proteins (PMPs) traffic from the endoplasmic reticulum (ER) to the peroxisome by a vesicular budding, targeting, and fusion process while peroxisomal matrix proteins are imported into the organelle by an autonomous, posttranslational mechanism. We highlight the contradictory conclusions reached to answer the question of how PMPs are inserted into the ER. We then review what we know and what still remains to be elucidated about the mechanism of PMP exit from the ER and the contribution of preperoxisomal vesicles to mature peroxisomes. Finally, we discuss discrepancies in our understanding of de novo peroxisome biogenesis in wild-type cells. We anticipate that resolving these key issues will lead to a more complete picture of peroxisome biogenesis.